The powers of law : a comparative analysis of sociopolitical legal studies / Mauricio García Villegas, National University of Colombia. - García-Villegas, Mauricio (Cambridge studies in law and society., 2018)
Comparative studies can reveal much about how law is formed out of social reality and political power by exploring these interactions in different national contexts. In this work Mauricio García-Villegas compares ideas about law and society in France and the United States, demonstrating different approaches to socio-political legal studies. Using the interdisciplinary tools of the sociology of law, critical legal theory, and socio-legal studies, García-Villegas builds up an insightful overview of what constitutes law and society theory and practice in France and the United States. He brings together diverse perspectives and practices that generally do not communicate well with one another, as is often the case between the critical theory of law of jurists and the legal sociology of sociologists. This study will allow readers to understand the sociology of law in a comparative perspective and sets out a new research agenda for the field of socio-political legal studies.